THE EFFECT OF TAX AVOIDANCE, CAPITAL STRUCTURE AND LIQUIDITY ON COMPANY VALUE WITH COMPANY SIZE AS A MODERATION VARIABLE IN INFRASTRUCTURE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE 2021-2023 PERIOD - Alin Riani; Amanti, Anggi Tias; Uliyah, Siti; Hakim, Mohamad Zulman; Hamdani; Hustna Dara Sarra (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to examine Tax Avoidance, Capital Structure, and Liquidity on Company Value, by considering Company Size as a Moderation variable, in infrastructure companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. The research population includes 69 companies, and through the purposive sampling technique, 24 companies were obtained as samples, Data analysis was carried out using E-views software 12. The result of F test show that F-value of 7.58699>2.51 of the f value of the r table and the Prob(F-statistic) value of 0.000000<0.05, it can be concluded that this model is feasible to use. The results of the study revealed that tax avoidance did not have a significant influence on the value of the company, the capital structure had a positive impact on the value of the company, while liquidity did not affect the value of the company. In addition, company size is not able to moderate the relationship between tax avoidance and company value, but it can moderate the relationship between capital structure and company value. However, company size cannot moderate the relationship between liquidity and company value.